Cognitive mechanisms in entrepreneurship - Baron, Robert A. (Journal of Business Venturing, 1998)
Because of their importance in creating wealth—both personal and societal—entrepreneurs have long been the subject of intensive study. Past research has focused on important issues such as: Why do some people, but not others, recognize or create new opportunities? Why do some, but not others, try to convert their ideas and dreams into business ventures? And why, ultimately, are some entrepreneurs successful and others not? Efforts to answer these questions in terms of the personal characteristics of entrepreneurs generally yielded disappointing results: contrary to what informal observation suggests, entrepreneurs do not appear to differ greatly from nonentrepreneurs with respect to various aspects of personality. As a result, a growing number of researchers have recently adopted a different approach—one emphasizing the role of cognitive processes in entrepreneurship. This perspective suggests that valuable insights into the questions posed above may be obtained through careful comparison of the cognitive processes of entrepreneurs and other persons. Whereas informative research has already been conducted within this framework, the present study seeks to expand this developing perspective by building additional conceptual bridges between entrepreneurship research and the large, extant literature on human cognition. Basic research on human cognition suggests that our cognitive processes are far from totally rational; in fact, our thinking is often influenced by a number of sources of potential bias and error. It is suggested here that entrepreneurs often work in situations and under conditions that would be expected to maximize the impact of such factors. Specifically, they face situations that tend to overload their information-processing capacity and are characterized by high levels of uncertainty, novelty, emotion, and time pressure. Together, these factors may increase entrepreneurs’ susceptibility to a number of cognitive biases. Several cognitive mechanisms that may exert such effects and that have not previously been considered in detail in the literature on entrepreneurship are examined. These include: counterfactual thinking—the effects of imagining what might have been; affect infusion—the influence of current affective states on decisions and judgments; attributional style—tendencies by individuals to attribute various outcomes to either internal or external causes; the planning fallacy—strong tendencies to underestimate the amount of time needed to complete a given project or the amount of work that can be achieved in a given time; and self-justification—the tendency to justify previous decisions even if they result in negative outcomes. Each mechanism is described, and specific hypotheses concerning its potential impact on the thinking of entrepreneurs are proposed. A final section of the article touches briefly on methods for testing hypotheses concerning these mechanisms and explores the implications of this cognitive perspective for future entrepreneurship research. This section emphasizes the fact that a cognitive perspective can provide researchers in the field with several new conceptual tools and may also facilitate the development of practical procedures for assisting entrepreneurs.